Nitrogen removal from poultry slaughterhouse wastewater in anaerobic-anoxic-aerobic combined reactor: Integrated effect of recirculation rate and hydraulic retention time. (1st February 2022) - Lopes, Carla Limberger; de Assis, Tatiane Martins; Passig, Fernando Hermes; Lima Model, Adriana Neres de; Mees, Juliana Bortoli Rodrigues; Cervantes, Francisco J.; Gotardo, Jackeline T.; Gomes, Simone Damasceno
Abstract: The aim of this work was to assess the nitrogen removal from slaughterhouse wastewater in an anaerobic-anoxic-aerobic combined reactor, evaluating the integrated effect of recirculation rate and hydraulic retention time. The recirculation of the liquid phase from the aerobic zone to the anoxic zone was applied to promote the denitrification through the use of endogenous electron donors. Three recirculation rates (R: 0.5, 1 and 2) and three hydraulic retention times (14, 11 and 8 h) were applied. The operation of the reactor was divided into 3 steps (I, II, and III) according to the factors evaluated (recirculation rate and HRT), to achieve operational conditions that would allow satisfactory performance in the different compartments of the reactor. During the experiment the reactor was fed with average total nitrogen (TN) and chemical oxygen demand (COD) of 65 mg L −1 and 580 mg L −1, respectively. The denitrification efficiency (theoretical) and kinetics parameters for COD decay were calculated. The highest performance was verified in the Step III (R = 2) and HRT of 11 h with NH4 + and TN removals of 84% and 65%, respectively. The TN removal efficiency (65%) was considered satisfactory, since the theoretical denitrification efficiency expected for this condition (R = 2) is 67%, without addition of an external carbon source. The lowest nitrification efficiency values were obtained in HRT of 8 h in the Step I and II (R = 0.5 and 1, respectively), indicating that the nitrification time (3 h - aerobic phase) may be the limiting factor in this HRT. The COD removal efficiency was high in all assays (>95%). The values of the kinetic degradation constants of organic matter were close for all recirculation rates, and the highest values were recorded for the HRT of 8 h and R = 1 and R = 2 (−0.48 and −0.43, respectively). Graphical abstract: Image 1 Highlights: The anaerobic-anoxic-aerobic combined reactor achieved satisfactory results. The best combination between Recycle rate and HRT tested it was 11 h and R of 2, 0. All COD and N removal was achieved with endogenous carbon and alkalinity sources.